Lattice normality and outer measures - Panagiotis D. Stratigos (International Journal of Mathematics and Mathematical Sciences)
A lattice space is defined to be an ordered pair whose first component is an arbitrary set X and whose second component is an arbitrary lattice L of subsets of X. A lattice space is a generalization of a topological space. The concept of lattice normality plays an important role in the study of lattice spaces.